(untitled) (Texas Journal of Philology, Culture and History, 2022)
This article analyzes the role of motivation in language learning, especially foreign language acquisition. The article indicates the importance of internal and external motivation for second language learners. Motivation plays an important role in the Foreign Language Learning process because it provides the first push to initiate a successful language learning process.